Issue in Design of Indonesian Traditional Ships - F.M., Mufti; Saputra, H.; Nofrizal, Nofrizal (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
Traditional ship-building is still widely practiced in Indonesia, Indonesia. Every province and regions has different characteristics in the design of ships in the traditional ships. The procedure to build traditional ships is far from the influence of technology. These provide a weakness on the safety for the design and operation. Current research seeks to promote a better understanding on design process in traditional shipbuilding in Bintan Island, Indonesia. The result is a comparison to current concept of design process in modern shipbuilding and recommendation for the traditional shipbuilding and local government.